Old age: the age of compensation against the age of deficits - Krainikov Е. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
This paper summarizes the results of research on the efficiency of cognitive functioning in later age. The analyzed data suggest a crucial role of personality and biographical factors that compensate for deficits due to age.